The reason for the widespread energetic storm particle event of 13 March 2023 - Dresing, N.; Jebaraj, I. C.; Wijsen, N.; Palmerio, E.; Rodriguez-Garcia, L.; Palmroos, C.; Gieseler, J.; Jarry, M.; Asvestari, E.; Mitchell, J. G.; Cohen, C. M. S.; Lee, C. O.; et al. (EDP Sciences, 2025)
Context. On 13 March 2023, when the Parker Solar Probe spacecraft (S/C) was situated on the far side of the Sun as seen from Earth, a large solar eruption took place, which created a strong solar energetic particle (SEP) event observed by multiple S/C all around the Sun. The energetic event was observed at six well-separated locations in the heliosphere, provided by the Parker Solar Probe, Solar Orbiter, BepiColombo, STEREO A, near-Earth S/C, and MAVEN at Mars. Clear signatures of an in situ shock crossing and a related energetic storm particle (ESP) event were observed at all inner-heliospheric S/C, suggesting that the interplanetary coronal mass ejection (CME)-driven shock extended all around the Sun. However, the solar event was accompanied by a series of pre-event CMEs.
Aims. We aim to characterize this extreme widespread SEP event and to provide an explanation for the unusual observation of a circumsolar interplanetary shock and a corresponding circumsolar ESP event.
Methods. We analyzed data from seven space missions, namely Parker Solar Probe, Solar Orbiter, BepiColombo, STEREO A, SOHO, Wind, and MAVEN, to characterize the solar eruption at the Sun, the energetic particle event, and the interplanetary context at each observer location as well as the magnetic connectivity of each observer to the Sun. We then employed magnetohydrodynamic simulations of the solar wind in which we injected various CMEs that were launched before as well as contemporaneously with the solar eruption under study. In particular, we tested two different scenarios that could have produced the observed global ESP event: (1) a single circumsolar blast-wave-like shock launched by the associated solar eruption, and (2) the combination of multiple CMEs driving shocks into different directions.
Results. By comparing the simulations of the two scenarios with observations, we find that both settings are able to explain the observations. However, the blast-wave scenario performs slightly better in terms of the predicted shock arrival times at the various observers.
Conclusions. Our work demonstrates that a circumsolar ESP event, driven by a single solar eruption into the inner heliosphere, is a realistic scenario.